Factors Influencing the Selection of Housing Location Post Earthquake 2007 in Solok - Fauzi, Fauzi (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Solok City is within range of the Sumatera active fault where destructive earthquakes have happened frequently (Padang Panjang earthquake 1926, Singkarak earthquake 1943 and 2004, and Solok earthquake 2007). Problems arise when most of the population often quickly forget the danger of future earthquakes and the mitigation efforts to reduce disaster hazards. New housings were still built in areas highly prone to earthquakes. The study investigated the factors affecting the locational choice for housing in post-earthquake Solok City using qualitative descriptive format. Post earthquake locational analysis of housing areas showed that cumulatively 47% of the houses were built in ‘high’ to ‘very high’ vulnerability area meaning that almost half of the houses built in the year 2010 are exposed to high risk from earthquakes. Analysis found four latent factors affecting the choice for housing location post 2007 Solok earthquake included (1) Earthquake Vulnerability, (2) House Prices, (3) Accessibility, and (4) Policy and Social factors. Analysis showed how earthquake vulnerability was indeed the priority factor in the choice of location for the general society. However this is contradictory to the reality of the current locations of housing areas built after the 2007 earthquake. The general society considered earthquake as very important but they built their houses in the disaster prone ares anyway. Therefore a common awareness needs to be established among all stakeholders to reduce the risks and improve mitigation efforts in case of future disasters.